Cracking the code: how piRNA pathway shapes spermatogenesis and combats male infertility - Hong, Zhidan; Huang, Sihan; Li, Li; Gao, Ying; Ma, Binyu; Fan, Qigang; Zhang, Yuanzhen; Wang, Mei (Frontiers in Cell and Developmental Biology, 2025)
Male infertility, accounting for approximately 50% of global infertility cases, is a growing concern in reproductive medicine. A fundamental cause lies in disrupted spermatogenesis—a complex, highly regulated process involving mitotic proliferation, meiotic division, and spermiogenic remodeling. Among the key regulatory pathways, PIWI-interacting RNAs (piRNAs) and their associated PIWI proteins have emerged as essential players in maintaining germline genome integrity and ensuring successful sperm development. However, their clinical relevance remain underexplored. This review provides a comprehensive synthesis of the piRNA pathway’s multifaceted roles across the full spectrum of spermatogenesis. We describe how piRNAs, together with PIWI proteins, silence transposable elements (TEs), guide chromatin remodeling, regulate mRNA translation, and protect sperm from environmental insults. We detail the stage-specific functions of piRNA machinery during spermatocytogenesis, spermatidogenesis, and spermiogenesis, supported by evidence from gene knockout models and cross-species studies. Particular emphasis is placed on piRNA biogenesis, including the primary processing pathway, the ping-pong amplification cycle, and terminal modifications mediated by enzymes such as PNLDC1 and TDRKH. Genetic disruptions in key piRNA pathway genes—including MOV10L1, PNLDC1, SPOCD1, and TDRKH—have been linked to clinical phenotypes such as non-obstructive azoospermia and severe oligozoospermia. We explore how these mutations impair piRNA maturation, compromise TE silencing, and trigger germ cell arrest, highlighting their diagnostic and therapeutic relevance. In addition, we discuss emerging applications of piRNAs as non-invasive biomarkers in seminal plasma, with altered piRNA profiles correlating with reduced sperm count and motility. Beyond pathogenesis, the piRNA pathway presents a promising frontier for reproductive interventions. We examine translational strategies targeting piRNA-associated proteins (e.g., RNF8-MIWI interaction modulators) and the potential for piRNA-guided gene silencing in germ cells. Moreover, we consider the impact of environmental toxins and epigenetic stressors on piRNA dynamics, suggesting new angles for fertility preservation. In summary, this review positions the piRNA pathway as a central regulator of male reproductive health. By integrating molecular biology with clinical genetics, we provide a roadmap for leveraging piRNA biology in the diagnosis, management, and treatment of male infertility.